2016
DOI: 10.1051/0004-6361/201527516
|View full text |Cite
|
Sign up to set email alerts
|

Dust properties across the CO snowline in the HD 163296 disk from ALMA and VLA observations

Abstract: Context. To characterize the mechanisms of planet formation it is crucial to investigate the properties and evolution of protoplanetary disks around young stars, where the initial conditions for the growth of planets are set. The high spatial resolution of Atacama Large Millimeter/submillimeter Array (ALMA) and Karl G. Jansky Very Large Array (VLA) observations now allows the study of radial variations of dust properties in nearby resolved disks and the investigation of the early stages of grain growth in disk… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
56
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 62 publications
8
56
1
Order By: Relevance
“…, so we assumed uniform priors from 0-10 au and 10-20 au, with the probability of h 10 au 0 > equal to one-third of the probability of h 10 au 0 < We also assumed a constant dust opacity throughout the disk. Previous multi-wavelength studies of disks at millimeter and centimeter wavelengths suggested radial variations in dust opacity due to grain growth (Isella et al 2010a; Banzatti Guilloteau et al 2011;Pérez et al 2012Pérez et al , 2015Trotta et al 2013;Menu et al 2014;ALMA Partnership et al 2015;Guidi et al 2016;Tazzari et al 2016). Similar radial variations may be present in our Upper Sco disks, and, in fact, are predicted by models of dust transport and evolution (e.g., Dullemond & Dominik 2005;Birnstiel et al 2010).…”
Section: Continuum Modelingsupporting
confidence: 85%
“…, so we assumed uniform priors from 0-10 au and 10-20 au, with the probability of h 10 au 0 > equal to one-third of the probability of h 10 au 0 < We also assumed a constant dust opacity throughout the disk. Previous multi-wavelength studies of disks at millimeter and centimeter wavelengths suggested radial variations in dust opacity due to grain growth (Isella et al 2010a; Banzatti Guilloteau et al 2011;Pérez et al 2012Pérez et al , 2015Trotta et al 2013;Menu et al 2014;ALMA Partnership et al 2015;Guidi et al 2016;Tazzari et al 2016). Similar radial variations may be present in our Upper Sco disks, and, in fact, are predicted by models of dust transport and evolution (e.g., Dullemond & Dominik 2005;Birnstiel et al 2010).…”
Section: Continuum Modelingsupporting
confidence: 85%
“…Previous ALMA observations showed that the continuum emission has a local maximum at about 90 A.U. [24], suggesting a dusty ring at a distance that corresponds to the frost line for CO molecules [25]. Recently, we have imaged the HD 163296 disk with ALMA at 0.2 00 angular resolution, a factor of 3 higher than previous observations and corresponding to a physical scale of 25 A.U.…”
mentioning
confidence: 82%
“…It is expected that the small dust grains seen in scattered light should be well-coupled with the gas for young disks, suggesting that the use of this surface density distribution is justified here. (See also the recent work by Guidi et al 2016 andPohl et al 2017 for HD 163296 and T Cha, respectively). The scale height is also defined as a power law in radius by…”
Section: Radiative Transfer Modeling With Mcfostmentioning
confidence: 95%